A method for setting environmental management reference concentration for human health protection and its application to the substances subject to PRTR - TAKANASHI, Rumi; URANO, Kohei; ITOYAMA, Keiko; KOBAYASHI, Takeshi; KAMEYA, Takashi (ENVIRONMENTAL SCIENCE, 2005)
In this study, methods for setting environmental management reference concentration in the air (CMA) and in the water (CMw) for protecting human health are proposed. CMA and CMW are defined as the concentrations at which continuous exposure to the human population is estimated to have no appreciable risk of adverse effects over a lifetime. CMA was estimated using the data from Japanese Air Quality Standard and guideline values, WHO Air Quality Guideline values, RfC and UR of the U.S. EPA, or the threshold limit values stated by the ACGIH or the Japan Society for Occupational Health. CMW was estimated using the data from Japanese Water Quality Standard and guideline values, WHO Water Quality Guideline values, ADI of the Japanese government or the JMPR, RID or UR of the U.S.EPA. A method to determine the contribution of drinking water to the total intake based on the physical properties of substances was developed to calculate the CMW using ADI or RfD. The CMA values of 185 substances and CMW values of 219 substances were obtained by applying this method to substances subject to PRTR. The method proposed and the data estimated in the present study will promote the self-management of facilities dealing with environmentally hazardous substances.